Can pyrolysis handle biomedical wastes?: Assessing the potential of various biomedical waste treatment technologies in tackling pandemics - Srivastava, Akshay; Sharma, Anita; Jena, Manoj Kumar; K Vuppaladadiyam, Arun; Reguyal, Febelyn; Joshi, Jyeshtharaj; Sharma, Abhishek; Shah, Kalpit; Gupta, Akhilendra; Chin, Bridgid Lai Fui; Saptoro, Agus; Sarmah, Ajit K (2024)
Globally, COVID-19 has not only caused tremendous negative health, social and economic impacts, but it has also led to environmental issues such as a massive increase in biomedical waste. The biomedical waste (BMW) was generated from centralized (hospitals, clinics, and research facilities) and extended (quarantine camps, COVID-19 test camps, and quarantined homes) healthcare facilities. Many effects, such as the possibility of infection spread, unlawful dumping/disposal, and an increase in toxic emissions by common BMW treatment facilities, are conjectured because of the rise in waste generation. However, it is also an opportunity to critically analyze the current BMW treatment scenario and implement changes to make the system more economical and environmentally sustainable. In this review, the waste disposal guidelines of the BMW management infrastructure are critically analyzed for many functional parameters to bring out possible applications and limitations of individual interventions. In addition, an investigation was made to select appropriate technology based on the environmental setting.